A practical manual of diabetic footcare - Edmonds, M. E; Foster, Alethea V. M; Sanders, Lee J (Blackwell Publishing, 2004)
Winner of ‘BMA Book of the Year’ in 2004Judges’ summary of the book:“This is a first-class text on the management of all aspects of the diabetic foot. It is a practical guide with information and advice, which is easy to access. It takes the reader through the natural history of the diabetic foot from the normal foot and relatively minor pathology to the end stage of infection, gangrene and ultimately amputation. The various stages with the book’s structure have case studies to highlight the clinical management problems encountered by diabetes foot specialists….Much of the text is broken up with bullet points, chapters and sub-chapters which allow the reader to pick out information from quick scans of the book. There is liberal use of illustrations throughout the book, which is particularly important as diabetic footcare is a specialty which is particularly reliant on observation. The book also details the ‘how to do it’ aspects rather than vague reference to what is required. It also uses the published evidence for its recommendations but, where this is lacking, the authors draw on their extensive experience of managing diabetic feet to guide the reader.”This book is a practical clinical manual for the diagnosis, treatment - both medical and surgical - and the long-term care of foot problems in people with diabetes. The authors are world-renowned experts in this subject and they present the internationally recognized best practice. The clinical chapters are presented in a structured, color-coded format to allow easy reference. The text also includes highlighted best clinical practice tips. Each chapter is accompanied by high-quality, full-color photographs that provide excellent examples of the earliest presenting signs as well as illustrating the step-by-step guidance on treatment. This book is an essential manual for every healthcare professional involved in the care of patients with diabetes.
Keywords: Diabetic Foot; Podiatry; diabetes mellitus; Diabetes Mellitus; nemoci nohy (od hlezna dolů); Foot Diseases; diabetická noha; podiatrie; diabetologie